Study on behavior of particle flow in the lid driven cavity based on various geometries - Nasir Ali, Mat Sani (2013)
This study is focusing on the behavior of particle flow in the lid driven cavity based on various geometries. The study is about to determine the fluid flow behavior in equilateral triangle and semi ellipse lid driven cavity shape. The silk particle is uses in the experiments are slightly buoyant towards water. Validation of flow was done by comparing the flow with past researchers. The fluid flow speed is ranging from Reynolds number of 1612, 2687 dan 5610 with various particle quantities. The flow is based on horizontal translating motion where the initial conditions of the particle remains at rest at the bottom wall of the lid driven cavity. The results shows for equilateral triangle shows that the silk particle behavior move to the preferential path and for semi ellipse lid driven cavities the silk particle behavior rotates in a swirling motion at the center of the lid driven cavity due to Taylor Gortler like vortices formations. The problem and recommendations for improvements are also being discuss in this thesis.